Effect of substrate offcut angle on BGaN epitaxial growth. (19th April 2016) - Ueyama, Kohei; Mimura, Hidenori; Inoue, Yoku; Aoki, Toru; Nakano, Takayuki
Abstract: Researchers expect the material BGaN to be useful in neutron detectors and ultraviolet (UV) light-emitting devices. In this study, we investigate the effect of the substrate offcut angle and polarity upon BGaN growth. In particular, BGaN is grown on top of GaN upon Al2 O3 substrates with various offcut angles. In the case of Ga-polar BGaN growth, the BN mole fraction increases as the offcut angle increases. Furthermore, as the offcut angle increases, the terrace width becomes reduced, which inhibits the formation of nuclei on the terrace and promotes the incorporation of B atoms at the step edges. Such incorporation is important at the step edge (which is the stable site) during BGaN growth because B atoms are easily desorbed from the surface and easily react in the gas phase. In the case of N-polar BGaN growth, the BN mole fraction exhibits different behavior in response to the offcut angle of the substrate. For this reason, the surface of N-polar BGaN is different from that of Ga-polar BGaN as it has facets of N-polar GaN and step bunching. These results indicate that the incorporation of B atoms at step edges significantly affects the BN mole fraction in BGaN growth.